A fluorescent probe for specific lysosome imaging in cells. Issue 19 (9th May 2017) - Jiang, Na; Wang, Bin; Zheng, Gengxiu; Xing, Yujing; Wang, Chunxiao; Wang, Qiufen
Abstract : Lyso-NA, a naphthalimide-based fluorescent probe, was synthesized. M-DPT was found to possess high specificity towards lysosome, superior photostability, and an appreciable tolerance to microenvironmental changes. Thus, this probe is a highly suitable imaging agent for targeting lysosome. Abstract : Herein, Lyso-NA, a naphthalimide-based fluorescent probe, was synthesized. M-DPT was found to possess high specificity towards lysosome, superior photostability, and an appreciable tolerance to microenvironmental changes. Thus, this probe is a highly suitable imaging agent for targeting lysosome.